Shape optimisation of stainless steel corrugated cylindrical shells for additive manufacturing - Zhang, Ruizhi; Meng, Xin; Gardner, Leroy (Engineering structures, 2022)
•Shape optimisation of axially compressed free-form wavy cylindrical shells conducted;•Optimised shell geometries analysed in terms of buckling resistance and imperfection sensitivity;•Optimisation framework based on Particle Swarm Optimisation algorithm fully described;•Effects of length and diameter-to-thickness ratio on the buckling resistance assessed;•Local buckling behaviour of other non-circular shell profiles examined; Axially compressed circular cylindrical shells with large diameter-to-thickness ratios are highly susceptible to local buckling, and their load-carrying capacities are known to be very sensitive to initial geometric imperfections. Hence, severe knock-down factors on their theoretical buckling loads are typically prescribed in design specifications, which greatly impair their structural efficiency. With the aim of enhancing load-bearing resistance and reducing sensitivity to imperfections, the shape optimisation and assessment of compressed free-form wavy cylindrical shells, the realisation of which is now viable through additive manufacturing, are the subject of the present study. The adopted optimisation framework employs the Particle Swarm Optimisation (PSO) algorithm, integrating computer-aided geometric design, nonlinear numerical simulations and imperfection sensitivity analyses. The structural performance of the optimised free-form wavy shells is analysed and compared to that of reference circular shells, as well as other types of non-circular shell profiles, including sinusoidally corrugated shells, Aster shells and stringer-stiffened shells. The optimised free-form wavy shell profiles are shown to exhibit increases in ultimate stress of up to 136% compared with the reference circular shell profiles; in general, greater benefits are achieved for more slender cross-sections. In future work, the proposed optimised shells will be manufactured in stainless steel by means of powder bed fusion (PBF), and their structural performance will be further verified through physical experiments.